ANALISIS PENGARUH PERTUMBUHAN DANA PIHAK KETIGA, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN, BIAYA OPERASIONAL DAN NET INTEREST MARGIN TERHADAP PROFITABILITAS BANK (Studi pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode 2010-2012) - Rachmawati, Mega Fitrah; Herawati, Juni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Increasing the measurement ability of the banking business to collect and distribute credit showed improved performance and health level of the bank. Health level of the banks can be seen from the financial performance, especially the performance of its profitability. The purpose of this study was to determine the effect of the growth of Third Party Funds, Loan to Deposit Ratio, Non-Performing Loans, Operating Costs and Net Interest Margin on Bank Profitability. The research object is the 13 commercial banks in Indonesia, which has a core capital above 5 trillion listed on the Indonesia Stock Exchange Period 2010-2012. The method of analysis used is multiple linear regression analysis. The results of the study of multiple linear regression analysis showed that the simultaneous growth variable Deposits, Loan to Deposit Ratio, Non-Performing Loans, Operating Costs and Net Interest Margin has a significant influence on bank profitability as measured by return on assets ratio. While partially, the variable growth of third party funds, non-performing loans and loan to deposit ratio had no significant influence on profitability, while Operating Costs and Net Interest Margin has significant influence on profitability. Based the five variables, the variable operating Â cost has dominant influence on the profitability of banks. This suggests that the level of bank efficiency in running its operations affect the level of income or